The Role of Bone Marrow Biopsy Morphology and Clinical Characteristics in Facing the Challenges of Diagnosing Primary Myelofibrosis, Polycythemia Vera, and Essential Thrombocythemia at Cipto Mangunkusumo Hospital - Rifani, Liyona; Stephanie, Agnes; Sukrisman, Lugyanti; Mira Lubis, Anna; Francisca Ham, Maria (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2023)
BackgroundMyeloproliferative neoplasm (MPN) is a neoplasm characterized by the proliferation of one or more myeloid cells and their derivatives. The limitations of molecular examination in Indonesia make the diagnosis of MPN based on clinical and histopathological examination very crucial. The aim evaluate the clinicopathological profile of primary myelofibrosis (PMF), polycythemia vera (PV), and essential thrombocythemia (ET) and identify the typical morphological characteristics of bone marrow biopsy.MethodsA retrospective study of cases diagnosed with MPN was conducted at the Department of Anatomic Pathology FMUI/RSCM in 2015-2019. Clinical data and evaluation of bone marrow morphology consisting of cellularity, erythroid myeloid ratio, cluster and megakaryocyte morphology, blast cells, fibrosis, osteosclerosis, and sinus dilatation were analyzed.ResultsA total of 172 cases were diagnosed as MPN BCR-ABL1-negative (PMF: 74; ET: 56; PV: 42). On routine blood examination, there was an increase in hemoglobin (Hb) and hematocrit (Ht) in PV, a decrease in Hb in PMF and an increase in platelets in ET (p<0.001). Splenomegaly is mostly found in PMF. Myeloid erythroid ratio was decreased in PV, normal in ET and increased in PMF (p<0.001). Megakaryocytes were arranged in loose clusters in 88.1% of PV cases and 96.4% of ET, dense clusters were found in 91.9% of PMF cases. Staghorn-like megakaryocytes were found in all ET cases and bulbous/cloud-like megakaryocytes were found in 97.3% of PMF cases. Most cases of PV (90.5%) and all cases of ET showed pre-fibrotic bone marrow (grade 0-1), while 77% of PMF cases showed fibrosis grade 2-3.ConclusionIn diagnosing PV, ET, and PMF, correlation between clinical data, laboratory, and bone marrow histomorphological evaluations, especially cellularity, myeloid:erythroid ratio, cluster and megakaryocyte morphology, degree of fibrosis, osteosclerosis, and sinus dilatation is required.